LITERARY REVIEW OF KAPHAJA YONI VYAPAD (NON SPECIFIC VULVO VAGINITIS) - Sarmah, *Smita; Baishya, Balen; Humtsoe, Yanbeni (International Journal of Ayurveda and Pharma Research, 2018)
A healthy woman is a promise of a healthy family. In different phases of a womans life, from puberty to menopause, the concept of healthy yoni has been mentioned in Ayurveda as well as in modern. Now a days, infection related to yoni is a burning problem irrespective of their age or socioeconomic status. Due to infection, there may be sign and symptoms like vaginal discharge, itching, coldness. in Ayurveda, these types of sign and symptoms are found in Kaphaja yoni vyapad and some of symptoms are similar with Non Specific Vulvovaginitis. Gynaecological disorders have found its immense importance in the field of medicine due to fact that women have a unique function of giving birth. In Ayurveda, women health care is related in separate section, where the term Yoni vyapad includes majority of gynaecological disorders. Before knowing the management, literature of the disease should be known. Therefore, in this study an effort has been put forth to make a conceptual study covering almost all the aspects of Kaphaja yoni vyapad as per Ayurveda as well as per modern.